2014
DOI: 10.12816/0007338
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Evaluation of Legislative Lawlessness in the Nigerian Budget Process

Abstract: The public sector budget in Nigeria, as in any other nation of the world, remains the most important policy thrust instrument or tool for different purposes including: economic, political, social and developmental. The Nigeria Federal budget has been facing a myriad of challenges dispossessing it of the powers to achieve its expected goals. Those problems include institutional, social and leadership dimensions. The unbridled legislative overbearing role in the Federal budget process is one of the emerging and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…71.74 percent disagreed that the government handles the nation's budgetary problems effectively while 79.71 percent disagreed that the management of the budget is very effective. This result is consistent with the findings of Nwankpa and Okeke, (2017);Igbara et al, (2016) and Olaoye (2014); they revealed that the Nigerian budgetary processes are characterised by indiscipline, deficient governance and implementation crises which have prevented the actualisation of the long-expected goals. They advocate for a disciplined-based process in the Nigerian budgetary system.…”
Section: Data Presentation For Nigeriasupporting
confidence: 92%
“…71.74 percent disagreed that the government handles the nation's budgetary problems effectively while 79.71 percent disagreed that the management of the budget is very effective. This result is consistent with the findings of Nwankpa and Okeke, (2017);Igbara et al, (2016) and Olaoye (2014); they revealed that the Nigerian budgetary processes are characterised by indiscipline, deficient governance and implementation crises which have prevented the actualisation of the long-expected goals. They advocate for a disciplined-based process in the Nigerian budgetary system.…”
Section: Data Presentation For Nigeriasupporting
confidence: 92%
“…Based on existing literature, there are quite some valuable theoretical perspectives surrounding the increasing and declining effects of oil revenues on the budgets of both oils importing and oil-exporting economies. The conventional theories of oil price are the main tenets of theories identified in the literature of oil revenue effects on the budgets of both oil-exporting and consuming nations (Hayes, 2015;Gosling, 2016;Al-Zeaud, 2015;Mupimpila et al 2015;Olaoye, 2014;Aladejare, 2014;Al-Qahtani et al, 2008;Reddick, 2003 andAl-Yousef, 1998;Sielke, 1995;Wilson and Sylvia, 1993;Linderoth, 1992;Downs and Rocke, 1984;Padgett, 1980). Principally, the research assessed three major theories upon which this research is based.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Another study which provided evidence for the ineffective use of budget for national developmental purposes was that conducted by Olaoye (2014). The author examined the effect of lawless legislative practices on budget process in Nigeria.…”
Section: Empirical Review Of Literaturementioning
confidence: 99%